Proposed A Web-Based Intelligent System to Manage the Blood Bank in Zakho District - Mohammed Ramadhan; Adel Al-zebari (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Due to the difficulty and rarity of the data tab in blood banks, information is often lost or forgotten. Because of this, it is important to have a number of different types of blood and know the total number of blood donors, as well as the number of units of blood imported and exported daily, monthly, or yearly. A web-based intelligent system is a web site that was created to manage the Zakho blood bank by using middleware languages like PHP that were used as transformer languages between MySQL databases as well as back-end web languages like HTML, CSS, and JavaScript that power up the front end, thus accelerating the management of blood import and export and accurately tabulating the blood donors' profiles so hospitals can get facilities that reduce the emergency cases that occur. Machine learning, deep learning, and an algorithm based on long short-term memory (LSTM) and based on time series have been used to predict an estimation of red blood cells (RBC) for periods (weekly, monthly, and yearly) that facilitate attracting the donors and importing and exporting the amount of blood that is needed in the future, and the algorithm produced these results (MAPE 3.259, MSE is 0.001, MAE is 0.031, RMSE is 0.042, and R-Squared is 0.913)